Comparative Determination of the Spectral Properties and Colloidal Behaviour of Humic Acids of Sal Forest Soils of Doon Valley Planted with Eucalyptus - Ghosh, R. C.; Singhal, R. M.; Pathak, T. C. (Indian Forester, 1977)
The conditions of Eucalyptus monoculture has promoted the formation of humic acids in soils with a clearly expressed aromatic rings as comapared to surrounding sal. Correspondingly the number of peripheral chains has decreased and the hydrophillic nature is less marked; humic acids are only slightly dispersed and coagulate even with small amounts of electrolyte.